Beyond the DSM : toward a process-based alternative for diagnosis and mental health treatment - Hayes, Steven C.; Hofmann, Stefan G. (Context Press, an imprint of New Harbinger Publications, Inc., 2020)
In this groundbreaking volume, two renowned experts in the field of psychology examine the ongoing efforts to move beyond the DSM diagnosis model to create a new, flexible treatment protocol--one that is tailored to clients' individual needs. With this book, clinicians and researchers will come away with a thorough understanding of process-based treatment, and how it can be implemented to improve human suffering and increase well-being.